The social construction of the bodies or the bodies of late capitalism - Kogan, Liuba (2024)
The text proposes to consider that invigorated, anorexic or bulimic bodies are borderline bodies: are the extremes of a scale where the central axle is the corporal ideal of slenderness in societies of the late capitalism. We start form the premise that bodies are social meaning producers and transmitters and that nutritional practices have always loaded with sense as social processes (support, pleasure, ritual, interchange, incorporation of the outside into the corporal interior). Nevertheless, socio-historical characteristics are analyzed allowing the understanding of relationships established by people with food and construction of the embodiment in traditional and modern societies, and late modernity.